Aging in 10 minutes: do age simulation suits mimic physical decline in old age? : comparing experimental data with established reference data - Gerhardy, Thomas; Schlomann, Anna; Wahl, Hans-Werner; Mombaur, Katja; Sloot, Lizeth H.; Schmidt, Laura (Experimental aging research, 2024)
Introduction: Age simulation suits are increasingly used in health care education. However, empirical evidence that quantifies the simulated performance losses in established geriatric tests and compares those declines with reference data of older adults is scarce. Methods: In a standardized lab setting, we compared performance of N = 61 participants (46 middle-aged, 15 young adults) with and without age simulation suit, for example in the Timed Up and Go Test (+dual task), Short Physical Performance Battery, grip strength, and 30-Second-Chair- Standing Test. Additionally, we compared the results with suit to established reference values of older adults in different age groups. Results: Reduced performance was observed in both groups when wearing the suit, yet to different degrees dependent on the assessment and user age. For one, larger declines were observed in more challenging and complex tasks across age groups. In addition, comparisons with reference values revealed age-differential “instant aging” effects. Discussion: A simulated “fourth age,” where frailty and impairments are accumulating, was not reached in the majority of assessments, especially not among younger participants. In conclusion, existing age simulation suits may have some educational and empathy potential, but so far, they fail in simulating the age period with most serious functional loss.